Method for preparing high-density nanophase magnesium alloy material

By preparing high-density nanophase magnesium alloy materials, including precise ingredients, molding, extrusion, pre-compression deformation and heat treatment, the problem of plasticity of magnesium alloy materials decreases when increasing strength is achieved, and the strength and plasticity of the material are achieved Coordinated improvement.

CN119491126APending Publication Date: 2025-02-21CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411626393.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the process of increasing the strength of existing magnesium alloy materials, the plasticity of existing magnesium alloy materials often decreases significantly, resulting in brittle fractures in actual applications, and microstructure regulation cannot achieve a coordinated improvement of plasticity and strength.

Method used

A method for preparing high-density nanophase magnesium alloy materials, including precise ingredients, heating and melting, molding, heating uniformization treatment, extrusion, pre-compression deformation treatment and heat treatment, etc., through these steps, the microstructure of magnesium alloys is regulated. , high density G.P. region and fine nanophase are formed.

Benefits of technology

The strength and plasticity of magnesium alloy materials have been improved simultaneously, the yield strength reaches 141MPa, and the ultimate compression rate reaches 31%. It is suitable for automobiles, aerospace, electronics and communication equipment, medical devices and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491126A_ABST
    Figure CN119491126A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-density nanophase magnesium alloy material, and the method specifically comprises the following steps: step 1, firstly carrying out precise batching, heating pure Mg until the pure Mg is molten, adding pure Zn, an Mg-Ca intermediate alloy and an Mg-Nd intermediate alloy after the pure Mg is molten, and simultaneously introducing inert protective gas; 2, the melt obtained in the step 1 is heated to be completely melted, then heat preservation and standing are conducted, and a magnesium alloy melt is obtained; 3, the magnesium alloy melt obtained in the step 2 is poured into a preheated mold to be formed, and a magnesium alloy ingot is obtained after cooling; 4, the magnesium alloy ingot obtained in the step 3 is heated and homogenized; 5, the magnesium alloy treated in the step 4 is extruded; 6, the magnesium alloy treated in the step 5 is subjected to heat treatment, and pre-compression deformation treatment is conducted; and 7, the magnesium alloy obtained in the step 6 is subjected to heat treatment, and the magnesium alloy material is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of magnesium alloys, and in particular to a method for preparing a magnesium alloy material having a high-density nanophase. Background Art

[0002] my country's magnesium ore resources account for more than 70% of the world's magnesium resources. It is a major producer and exporter of magnesium alloy materials and has significant strategic advantages. From the perspective of lightweight, the density of magnesium alloy is low, only one-fourth of steel and two-thirds of aluminum alloy. It can greatly reduce the weight of products at the same strength, which helps to improve automobile fuel efficiency, reduce energy consumption and environmental pollution, and is an important material for achieving energy conservation, emission reduction and green development.

[0003] In the fields of aerospace, transportation, oil and gas extraction, and medical equipment, magnesium alloys have significant application advantages. These fields often have strict requirements on the mechanical properties of materials, requiring both high strength to withstand complex working environments and good plasticity to ensure the machinability and safety of materials. However, a core problem of traditional magnesium alloys is the contradiction between strength and plasticity. In order to improve the strength of magnesium alloys, the method commonly used in the prior art is precipitation strengthening. In order to achieve a greater precipitation strengthening effect, it is often necessary to add a high content of alloying elements. Although this strategy can significantly improve the strength of the material, the addition of a high content of alloying elements will induce the precipitation of a larger second phase, increase the stress concentration inside the material, and reduce the ability of plastic deformation. At the same time, the crystal structure of magnesium alloys determines that it has poor plasticity at room temperature, especially in the process of increasing strength, the plasticity tends to drop significantly. This means that when the strength of magnesium alloys is improved by adding alloying elements or changing the processing technology, the ductility and toughness of the material will be affected, resulting in the material being prone to brittle fracture in practical applications. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a method for preparing a high-density nanophase magnesium alloy material, so as to solve the problem in the prior art that microstructure regulation cannot achieve a coordinated improvement in plasticity and strength.

[0005] In order to solve the above technical problems, this application adopts the following technical solutions:

[0006] A method for preparing a high-density nanophase magnesium alloy material comprises the following steps:

[0007] Step 1: First, accurately batch the ingredients, heat pure Mg until it is melted, add pure Zn, Mg-Ca master alloy and Mg-Nd master alloy after melting, and introduce inert protective gas at the same time;

[0008] Step 2: heating the melt obtained in step 1 to completely melt it, and then keeping it at the temperature for 20-30 minutes to obtain a magnesium alloy melt;

[0009] Step 3: pouring the magnesium alloy melt obtained in step 2 into a preheated mold to form a magnesium alloy ingot after cooling;

[0010] Step 4: heating and homogenizing the magnesium alloy ingot obtained in step 3;

[0011] Step 5: extruding the magnesium alloy treated in step 4 at 350° C. to 450° C., with an extrusion rate of 1 to 10 mm / s and an extrusion ratio of 10 to 50;

[0012] Step 6: The magnesium alloy treated in step 5 is subjected to a heat treatment at 300°C-450°C for 1-12 hours, and subjected to a pre-compression deformation treatment; wherein, the pre-compression deformation is 1%-15% calculated according to the percentage of length change, and the strain rate is 10 -2 ~10 -4 / s;

[0013] Step 7: heat-treating the magnesium alloy obtained in step 6 to obtain the magnesium alloy material.

[0014] Preferably, in step 1, pure Mg is smelted at 700°C to 720°C; the inert gas is a mixture of CO2 and SF6; after the inert protective gas is introduced, the temperature is kept at 650°C to 700°C for 20 to 40 minutes.

[0015] Preferably, in the mixed gas, the volume ratio of CO2 and SF6 is (200-400):1.

[0016] Preferably, in step 2, the melt is heated to 720° C. to 750° C. and then kept warm.

[0017] Preferably, in step 3, the mold is preheated to 200°C to 350°C.

[0018] Preferably, in step 4, the conditions for the heating homogenization treatment are: homogenization treatment at 400° C. to 480° C. for 8 h to 24 h.

[0019] Preferably, in step 7, the heat treatment is: keeping warm at 100° C. to 260° C. for 2 h to 24 h.

[0020] Preferably, calculated by mass percentage, in the magnesium alloy material, the Zn content is 0.5% to 1%, the Ca content is 0.1% to 0.3%, the Nd content is 0.3% to 0.6%, and the remainder is magnesium and unavoidable impurity elements.

[0021] Preferably, the ultimate compression rate of the magnesium alloy material at room temperature is at least 30%.

[0022] Compared with the prior art, this application has the following beneficial effects:

[0023] 1. The present application has made adjustments to the preparation method of magnesium alloys. The present application has found that after the fifth step of extrusion treatment, pre-compression deformation treatment and heat treatment can simultaneously improve the strength and plasticity of the magnesium alloy material, and a large number of dislocations, stacking faults and twins are formed inside the magnesium alloy material by pre-compression deformation treatment. The presence of dislocations can increase the work hardening effect of the material, thereby improving its yield strength; while stacking faults and twins can effectively prevent the movement of dislocations, further enhancing the material's ability to resist deformation; but pre-compression deformation alone is not enough, because excessive dislocations and other defects may cause material embrittlement; therefore, it is particularly important to perform annealing heat treatment on the magnesium alloy material immediately after pre-compression deformation treatment; during the heat treatment process, the increase in temperature allows atoms to obtain sufficient energy to overcome diffusion barriers, which prompts alloying elements (such as Zn, Ca, Nd) to segregate along defect paths (such as stacking faults and twin interfaces) inside the material. This segregation phenomenon helps to form highly dispersed GP zones (Guinier-Preston zones) in the matrix, that is, nanoscale regions enriched with specific alloying elements, and enriched zones of solid solution atoms at twin boundaries. Due to the formation of highly dispersed GP zones, they can act as obstacles to dislocation movement, effectively hindering the slip of dislocations, thereby enhancing the tensile strength of the material. At the same time, since the distribution of GP zone and solid solution atoms is very small and uniform, they will not cause stress concentration like coarse second phase particles, but will help to improve the plasticity of the material. In addition, the segregation of solid solution atoms at the twin boundary can also stabilize the twin boundary and reduce its movement when stressed, which is crucial for maintaining the microstructural integrity of the material and improving its plastic deformation ability. Therefore, the present application combines the method of annealing heat treatment with compression prestrain, which can not only introduce abundant micro defects in the alloy, but also promote the effective segregation of alloying elements, and finally achieve a significant improvement in material strength and plasticity.

[0024] 2. The strength and plasticity of the magnesium alloy material obtained after the treatment of this application are improved at the same time. The yield strength of the magnesium alloy material obtained after the treatment reaches 141MPa, and the ultimate compression rate reaches 31%, which makes it have good application prospects in the fields of automobiles, aerospace, electronic and communication equipment, medical equipment, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1These are low-magnification HAADF-STEM and BF-STEM images of the alloys of Comparative Example 2 and Example 4; wherein a and c are for Comparative Example 2, and b and d are for Example 4; the grain boundaries are represented by small black arrows, and the twin boundaries are represented by small red arrows.

[0026] Figure 2 These are the FFT images, BF-STEM images and HAADF-STEM images of the alloy of Example 4; wherein a and b are BF-STEM images, c and e are HAADF-STEM images, and d and f are FFT images.

[0027] Figure 3 This is the BF-STEM image of Comparative Example 1.

[0028] Figure 4 It is a graph showing the changes in mechanical properties of Comparative Example 1 and Examples 2 to 4; wherein a is a typical compression engineering stress-strain curve, and b is the changes in mechanical property parameters. DETAILED DESCRIPTION

[0029] This application will combine the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on this application belong to the scope of protection of this application.

[0030] Unless otherwise indicated in specific cases in this application, the numerical ranges listed herein include the upper and lower limits, as well as all integers and fractions within the range, and are not limited to the specific values ​​listed when defining the range.

[0031] 1. A method for preparing a magnesium alloy material having a high density nanophase

[0032] Step 1: First, accurately batch the ingredients, heat pure Mg until it is melted, add pure Zn, Mg-Ca master alloy and Mg-Nd master alloy after melting, and introduce inert protective gas at the same time;

[0033] Step 2: heating the melt obtained in step 1 to completely melt it, and then keeping it at the temperature for 20 to 30 minutes to obtain a magnesium alloy melt;

[0034] Step 3: pouring the magnesium alloy melt obtained in step 2 into a preheated mold to form a magnesium alloy ingot after cooling;

[0035] Step 4: heating and homogenizing the magnesium alloy ingot obtained in step 3;

[0036] Step 5: extruding the magnesium alloy treated in step 4 at 350° C. to 450° C., with an extrusion rate of 1 to 10 mm / s and an extrusion ratio of 10 to 50;

[0037] Step 6: The magnesium alloy treated in step 5 is subjected to a heat treatment at 300°C to 450°C for 1 to 12 hours, and subjected to a pre-compression deformation treatment; wherein, the pre-compression deformation is 1% to 15% calculated according to the percentage of length change, and the strain rate is 10 -2 ~10 -4 / s;

[0038] Step 7: heat-treating the magnesium alloy obtained in step 6 to obtain the magnesium alloy material.

[0039] After studying the prior art, the present application found that in the traditional magnesium alloy preparation method, during the smelting process, the magnesium alloy is easy to react with oxygen in the air to form oxide inclusions, which will reduce the mechanical properties of the material, especially the plasticity and fatigue properties. At the same time, the preparation method of the magnesium alloy material cannot regulate the internal microstructure of the alloy, which easily leads to uneven internal microstructure of the alloy, and cannot correctly and effectively utilize the defects such as segregation, dislocation and twinning formed, resulting in these defects often having adverse effects, which ultimately affects the simultaneous improvement of the strength and plasticity of the magnesium alloy material. The present application considers adjusting the magnesium alloy preparation method, and through the improvement of the method process, it realizes the regulation of the internal microstructure of the magnesium alloy, so that it can bring about a common improvement in the strength and plasticity of the magnesium alloy material.

[0040] In some embodiments of the present application, the present application obtains an extruded magnesium alloy after processing by step 5, because compared with the cast state, the extruded alloy has fewer internal defects, better comprehensive mechanical properties, and is more conducive to subsequent processing. In step 5, the magnesium alloy treated in step 4 is extruded at 350°C to 450°C. If the temperature is too high, the surface of the extruded bar will be overburned, increasing the surface defects of the alloy, and the dimensional accuracy of the alloy bar will be seriously affected. If the temperature is too low, the alloy bar is difficult to deform, the extrusion process is difficult to achieve, and a qualified alloy bar cannot be obtained. Therefore, the temperature of magnesium alloy extrusion can be 350°C, 400°C, 450°C, etc., and all ranges and sub-ranges between the above values; the extrusion rate is controlled at 1 to 10 mm / s, and extrusion too slow will cause abnormal growth of grains in the organization, while affecting the surface quality of the alloy bar; extrusion too fast will cause incomplete recrystallization of the organization, increase the content of organizational defects, and affect the plasticity of the alloy bar. Therefore, the extrusion rate of the magnesium alloy can be 1mm / s, 2mm / s, 3mm / s, 4mm / s, 5mm / s, 6mm / s, 7mm / s, 8mm / s, 9mm / s, 10mm / s, etc., and all ranges and sub-ranges between the above values; at the same time, the extrusion ratio is controlled between 10 and 50. Too low an extrusion ratio will affect the recrystallization behavior of the alloy and reduce the extrusion effect; too high an extrusion ratio will make it difficult to extrude, increase the internal stress of the rod, and cause the alloy rod to undergo early aging during the deformation process, which is not conducive to the subsequent processing of the magnesium alloy material. Therefore, the extrusion ratio can be 10, 15, 20, 25, 30, 35, 40, 45, 50, etc., and all ranges and sub-ranges between the above values; it should be understood that in the implementation scheme, any of the above ranges can be combined with any range of other reaction conditions in the present invention.

[0041] In some embodiments of the present application, the present application sets step 6, the purpose of which is to further homogenize the composition of the extruded rod on the one hand, and to regulate the defect content in the organization by pre-compression on the other hand, so as to optimize the subsequent step 7 low-temperature aging precipitation behavior. The present application applies a certain compressive stress to the magnesium alloy material through pre-compression treatment to cause permanent deformation. In this process, a large number of dislocations, stacking faults and twins will be formed inside the magnesium alloy material. These microscopic defects are not only the main carriers of plastic deformation of the material, but also an important factor affecting its mechanical behavior. The existence of these dislocation structures can increase the internal stress of the material, thereby increasing its yield strength; while stacking faults and twins can effectively prevent the movement of dislocations, further enhance the material's resistance to deformation, thereby weakening the adverse effects of these microscopic defects, and playing its role in simultaneously improving the strength and plasticity of the magnesium alloy material. The present application heat treats the magnesium alloy after step 5 at 300℃~450℃ for 1~12h. If the heat treatment temperature is too high at this time, the alloy will be overburned, thereby affecting the quality of the alloy, but if the heat treatment temperature is too low, the homogenization effect will be reduced. Therefore, the heat treatment temperature is 300℃, 350℃, 400℃, 450℃, etc., and all ranges and sub-ranges between the above values; if the heat treatment time is too short, the homogenization effect cannot be achieved, and if it is too long, it will have an adverse effect on the magnesium alloy material, resulting in a reduction in the homogenization effect. Therefore, the heat treatment time is 1h, 4h, 8h, 10h, 12h, etc., and all ranges and sub-ranges between the above values; next, the magnesium alloy material is subjected to pre-compression deformation treatment at the heat treatment temperature; wherein, calculated according to the percentage of length change, the pre-compression deformation amount is 1% to 15%, and the strain rate is 10 -2 ~10 -4 / s. The present application found that too small a pre-compression deformation will lead to insufficient defect introduction and affect the precipitation strengthening effect; while too large a pre-compression deformation will lead to excessive defects such as twins and dislocations, thus affecting the plasticity of the alloy. Therefore, calculated according to the percentage of length change, the pre-compression deformation can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc., as well as all ranges and sub-ranges between the above values; not only the pre-compression deformation should be controlled, but also the strain rate should be controlled to be within 10 -2 ~10 -4 / s, because too slow a strain rate will lead to a long loading time and affect processing efficiency; too fast a strain rate will lead to excessive concentration of stress inside the material and cause material failure. Therefore, the strain rate is 10 -2 / s, 10 -3 / s, 10 -4 / s, etc., and all ranges and sub-ranges between the above numerical values; it should be understood that, in embodiments, any of the above ranges can be combined with any ranges of other reaction conditions in the present invention.

[0042] In some embodiments of the present application, in step 1, pure Mg is smelted at 700°C to 720°C; the inert gas is a mixed gas of CO2 and SF6; after the inert protective gas is introduced, the temperature is kept at 650°C to 700°C for 20 to 40 minutes. In the mixed gas, the volume ratio of CO2 to SF6 is (200 to 400):1. The pure Mg smelting temperature can be 700°C, 710°C, 720°C, etc., and all ranges and sub-ranges between the above values; under the protection of inert protective gas, the holding temperature can be 650°C, 680°C, 700°C, etc., and all ranges and sub-ranges between the above values; the holding time can be 20min, 30min, 40min, etc., and all ranges and sub-ranges between the above values; in the mixed gas, the volume ratio of CO2 and SF6 can be 200:1, 300:1, 400:1, etc., and all ranges and sub-ranges between the above values; it should be understood that in the implementation scheme, any of the above ranges can be combined with any range of other reaction conditions in the present invention.

[0043] In some embodiments of the present application, in step 2, the melt is heated to 720°C to 750°C, and then kept warm. The melt can be heated to 720°C, 730°C, 750°C, etc., and all ranges and sub-ranges between the above values; it should be understood that in the embodiment, any of the above ranges can be combined with any range of other reaction conditions in the present invention.

[0044] In some embodiments of the present application, in step 3, the mold is preheated to 200° C. to 350° C. The mold can be preheated to 200° C., 300° C., 350° C., etc., and all ranges and sub-ranges between the above values; it should be understood that in an embodiment, any of the above ranges can be combined with any range of other reaction conditions in the present invention.

[0045] In some embodiments of the present application, in step 4, the conditions for the heating homogenization treatment are: homogenization treatment at 400°C to 480°C for 8h to 24h. In this step, if the heating homogenization treatment temperature is too low, the eutectic structure will not be easily melted, affecting the homogenization effect; and if the heating homogenization treatment temperature is too high, the material surface will be overburned and the quality requirements of the heat-treated material cannot be met. Therefore, the heating homogenization treatment temperature is 400°C, 440°C, 450°C, 460°C, 480°C, etc., and all ranges and sub-ranges between the above values; the homogenization treatment time can be 8h, 12h, 24h, etc., and all ranges and sub-ranges between the above values; it should be understood that in the embodiment, any of the above ranges can be combined with any range of other reaction conditions in the present invention.

[0046] In some embodiments of the present application, step 7 is also crucial in the present application, because after the pre-compression deformation treatment of step 6, the heat treatment can enable the atoms inside the magnesium alloy material to obtain enough energy to overcome the diffusion barrier, which promotes the alloying elements (such as Zn, Ca, Nd) to be segregated along the defect paths (such as stacking faults and twin interfaces) inside the material. This segregation phenomenon helps to form highly dispersed GP zones (Guinier-Preston zones) in the matrix, that is, nanoscale regions enriched with specific alloying elements, and enriched zones of solid solution atoms at twin boundaries. The formation of GP zones plays an important role in improving the strength of magnesium alloy materials, because these structures can serve as obstacles to dislocation movement, effectively hindering the slip of dislocations, thereby enhancing the tensile strength of the material. At the same time, since the distribution of GP zones and solid solution atoms is very small and uniform, they will not cause stress concentration like coarse second phase particles, but will help to improve the plasticity of the material. In addition, the segregation of solute atoms at the twin boundaries can also stabilize the twin boundaries and reduce their movement when subjected to stress, which is crucial to maintaining the microstructural integrity of the material and improving its plastic deformation capacity. In step 7, the heat treatment is: keeping warm at 100°C to 260°C for 2h to 24h. If the heat treatment time is too short or the temperature is too low, it is difficult for the solute atoms to fully diffuse to form a precipitate phase; if the heat treatment time is too long or the temperature is too high, the precipitate phase will grow abnormally, affecting the precipitation effect of the nanophase. Therefore, the heat treatment temperature can be 100°C, 150°C, 200°C, 260°C, etc., and all ranges and sub-ranges between the above values; the holding time can be 2h, 4h, 8h, 12h, 16h, 20h, 24h, etc., and all ranges and sub-ranges between the above values; it should be understood that in the embodiment, any of the above ranges can be combined with any range of other reaction conditions in the present invention.

[0047] In some embodiments of the present application, calculated by mass percentage, in the magnesium alloy material, the Zn content is 0.5% to 1%, the Ca content is 0.1% to 0.3%, the Nd content is 0.3% to 0.6%, and the balance is magnesium and unavoidable impurity elements. Calculated by mass percentage, in the magnesium alloy material, the Zn content can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc., and all ranges and sub-ranges between the above values; the Ca content can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, etc., and all ranges and sub-ranges between the above values; the Nd content can be 0.3%, 0.4%, 0.5%, 0.6%, etc., and all ranges and sub-ranges between the above values; it should be understood that in the embodiment, any of the above ranges can be combined with any range of other reaction conditions in the present invention.

[0048] In some embodiments of the present application, the ultimate compression rate of the magnesium alloy material at room temperature is at least 30%.

[0049] 2. Examples and Comparative Examples

[0050] Example 1

[0051] Step 1: Precisely proportion the amount of each component, melt pure Mg at 700℃~720℃, add pure Zn, Mg-Ca master alloy and Mg-Nd master alloy after melting, and introduce inert gas protection into the furnace at 650℃~700℃ for 30min. Among them, calculated by mass percentage, the Zn content is 0.6wt%, the Ca content is 0.2wt%, the Nd content is 0.4wt%, and the balance is Mg and unavoidable impurities. Calculated by volume percentage, the volume ratio of CO2 and SF6 in the inert gas is 300:1.

[0052] Step 2: The furnace continues to heat up to 720°C ~ 750°C, slowly stir, and after the alloy is melted, keep it warm and let it stand for 20 minutes to obtain a magnesium alloy melt.

[0053] Step 3: Pour the magnesium alloy melt obtained in step 2 into a preheated mold at 200° C. to 350° C., and obtain a magnesium alloy ingot after cooling.

[0054] Step 4: The magnesium alloy ingot obtained in step 3 is homogenized at 400°C for 8 hours.

[0055] Step 5: The homogenized magnesium alloy obtained in step 4 is extruded at 450° C. with an extrusion rate of 2 mm / s and an extrusion ratio of 25.

[0056] Step 6: The magnesium alloy obtained in step 5 is subjected to heat treatment at 400°C for 1 h and pre-compressed with a pre-compressed deformation amount of 1% and a strain rate of 10 -3 / s.

[0057] Step 7: The magnesium alloy obtained in step 6 is heat treated at 200°C for 8 hours.

[0058] Example 2

[0059] The adjustment was made on the basis of Example 1, except that the pre-compression deformation was 2.5%, and the remaining steps were exactly the same as Example 1. The obtained magnesium alloy material was marked as 1#2.5c-8a.

[0060] Example 3

[0061] The adjustment was made on the basis of Example 1, except that the pre-compression deformation was 4%, and the other steps were exactly the same as Example 1. The obtained magnesium alloy material was marked as 1#4c-8a.

[0062] Example 4

[0063] The adjustment was made on the basis of Example 1, except that the pre-compression deformation was 6%, and the other steps were exactly the same as Example 1. The obtained magnesium alloy material was marked as 1#6c-8a.

[0064] Comparative Example 1

[0065] The adjustment is made on the basis of Example 1, except that: after step 5 is completed, step 7 is directly performed without step 6; the operating conditions of each step are exactly the same as those of Example 1. The obtained magnesium alloy material is marked as 1#8a.

[0066] Comparative Example 2

[0067] The adjustment is made on the basis of Example 4, except that: after step 5 is completed, only step 6 is performed, and step 7 is no longer performed; the operating conditions of each step are exactly the same as those of Example 4. The obtained magnesium alloy material is marked as 1#6c.

[0068] 3. Performance Comparison

[0069] This application focuses on the impact of step 6 and step 7 on the structure of magnesium alloy materials. After observing the microscopic morphology of the magnesium alloy materials obtained by the embodiment and the comparative example, it is found that:

[0070] (1) Figure 1 As shown, the alloy materials obtained in Comparative Example 2 and Example 4 both have lens structures, which are generally considered to be twin structures, such as Figure 1In the magnesium alloy material obtained in Comparative Example 2, the twin boundary is clear and the contrast is uniform, as shown in FIG. Figure 1 As shown by the red arrow in a. In the magnesium alloy material obtained in Example 4, the bright white nanodots are enriched in the twin boundaries and grain boundaries, such as Figure 1 As shown by the black and red arrows in b, this indicates that the solute atoms are segregated at the planar defects. From the BF-STEM, it can be seen that high-density dislocations and a small amount of second phases were found in Comparative Example 2, such as Figure 1 c. In contrast, a large amount of nanophases were produced in Example 4, and the average size of the nanophase precipitates was between 2 and 20 nm, as shown in FIG. Figure 1 d. It can be seen that step 7 will induce the alloy elements to form segregation at the surface defects and precipitate in the form of a large number of nanophases.

[0071] (2) Figure 2 The precipitation phase characteristics of the alloy in Example 4 are further described, such as Figure 2 As shown in a, two nanophases are formed on the base surface. One of them is a high-density, extremely fine needle-like nanophase that is parallel to each other, with a length of 5 to 10 nm and a thickness of less than 1 nm, such as Figure 2 As shown by the white arrow in b, the other nanophase exhibits a relatively large size and sparse distribution, with a length of 100–200 nm and a thickness of less than 1 nm, as shown in Figure 2 As shown by the yellow arrow in b. High-resolution HAADF-STEM shows that the solute atoms of Example 4 are segregated into one atomic layer of the basal plane, as shown in Figure 2 c. These nanophases with completely coherent internal atomic order are called GP regions. Large-sized nanophases are composed of multiple GP regions connected in front and behind, such as Figure 2 As shown in the high-resolution HAADF-STEM in e. In the high-resolution HAADF-STEM image, the contrast of the large-sized nanophase is more obvious than that of the fine GP region, indicating that the segregation of solute atoms in the large-sized precipitates is greater. Figure 2 [11-20] in (d, f) a-Mg It can be seen from the diffraction pattern that there are obvious stripes between the diffraction spots along the c-axis, which indicates that there are potential basal plane stacking faults or basal plane precipitation phases, such as γ and γ', in the magnesium alloy material of Example 4.

[0072] (3) It can be seen from the above analysis that after the magnesium alloy is treated in step 6, a large number of defects such as dislocations and twins are generated in the matrix. The presence of these defects will induce the alloy elements to segregate at the twin boundaries after the treatment in step 7, and form a high-density GP zone at the same time. Since the alloy elements are segregated at the twin boundaries, the twin boundaries remain stable during the entire deformation process, thereby improving the strength of the magnesium alloy material. At the same time, the nanophase in the GP zone and the matrix is ​​induced to precipitate and strengthen, and the interaction between the GP zone and the dislocation promotes the dislocation rearrangement and slip, thereby synergistically improving the strength and ductility of the magnesium alloy. Therefore, the alloy prepared by this application has a synergistic effect of strength and toughness.

[0073] (4) However, if step 7 is performed directly after step 5, the content of precipitated phase in the alloy will be reduced, and the size of the precipitated phase will be larger. In this case, the size of the precipitated phase is basically maintained between 200nm and 2μm, and the precipitated phase precipitates along the grain boundary, which will greatly weaken the simultaneous improvement of strength and plasticity of magnesium alloy materials. This also further proves that steps 6 and 7 are key steps to regulate the formation of alloy elements at the twin boundary and the precipitation of high-density nanophases.

[0074] (5) Combination Figure 4 The changes in mechanical properties shown are experimentally studied on magnesium alloys under different pre-strain degrees and heat treatment conditions, and it is found that the compressive yield strength of comparative example 1 is 59MPa and the ultimate compressive strain is 31.03%. In contrast, the compressive yield strengths of Examples 2 to 4 are 94MPa, 117MPa and 141MPa, respectively, and the ultimate compressive strains are 34.21%, 31.47% and 31.68%, respectively. These data show that with the increase in the degree of pre-strain, the yield strength of the magnesium alloy is significantly improved, and the plasticity is also improved to a certain extent. From the perspective of microstructure, the content of the precipitated phase in the 1#8a alloy is less and the size is larger, usually between 200nm and 2μm, and mainly precipitates along the grain boundaries. Although this large-sized precipitate can increase the hardness of the material, its contribution to plasticity is limited. On the contrary, the size of the precipitated phase in the alloy obtained in the embodiment is smaller and the density is larger, usually between 2 and 20nm, and is evenly distributed in the material. These fine precipitates not only increase the strength of the material, but also promote the rearrangement and slip of dislocations by interacting with them, thereby improving the plasticity of the material.

[0075] In summary, in the method described in the present application, further optimization treatment is performed by performing steps 6 and 7 to achieve higher strength and plasticity. Step 6 pre-strain treatment, that is, the extruded magnesium alloy is subjected to different degrees of compression pre-deformation. The main purpose of the pre-strain treatment is to introduce a large number of microscopic defects such as dislocations and twins into the material. These defects not only increase the internal stress of the material, but also provide favorable conditions for subsequent heat treatment. With the increase of the degree of pre-strain, the dislocation density and the number of twins inside the material increase significantly. The presence of these defects provides a path for the segregation of alloying elements and promotes the aggregation of solute atoms on the dislocation and twin interfaces. Subsequently, step 7 heat treatment is performed, that is, heat treatment is performed for 2 to 24 hours in a temperature range of 100°C to 260°C. During the heat treatment process, the increase in temperature enables the alloying elements to obtain sufficient energy, so that they can be segregated along the dislocation and twin interfaces. This segregation phenomenon is manifested in the microstructure as the enrichment of solute atoms at the twin boundaries and grain boundaries, forming a high-density GP zone (Guinier-Preston zones) and a fine nanophase. GP zones are enriched areas formed by solute atoms in the matrix. These areas have different chemical compositions and crystal structures from the matrix, which can effectively hinder the movement of dislocations, thereby improving the strength of the material. In addition, the nanophases formed during the heat treatment process also have an important influence on the properties of the material. These nanophases are usually 2 to 20 nm in size and are evenly distributed in the material. The presence of nanophases not only increases the hardness and strength of the material, but also promotes the rearrangement and slip of dislocations through interaction with dislocations, thereby improving the plasticity of the material. This synergistic effect allows the material to maintain good ductility while increasing its strength.

[0076] The combination of pre-strain treatment and heat treatment adopted in this application is a key step in optimizing the microstructure and performance of magnesium alloys. Pre-strain treatment provides favorable conditions for subsequent heat treatment by introducing a large number of microscopic defects. During the heat treatment process, alloy elements are segregated at these defects to form high-density GP zones and fine nanophases. These changes in microstructure significantly improve the strength and plasticity of magnesium alloys. Therefore, by reasonably controlling the degree of pre-strain and heat treatment conditions, the synergistic improvement of strength and plasticity of magnesium alloy materials can be achieved, thereby meeting the needs of different application scenarios.

[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the technical solution. Ordinary technicians in this field should understand that those modifications or equivalent substitutions of the technical solution of the present application that do not depart from the purpose and scope of the technical solution of the present application should be included in the scope of the claims of the present application.

Claims

1. A method for preparing a high-density nanophase magnesium alloy material, characterized in that: The specific steps include: Step 1: First, accurately batch the ingredients, heat pure Mg until it is melted, add pure Zn, Mg-Ca master alloy and Mg-Nd master alloy after melting, and introduce inert protective gas at the same time; Step 2: heating the melt obtained in step 1 to completely melt it, and then keeping it at the temperature for 20 to 30 minutes to obtain a magnesium alloy melt; Step 3: pouring the magnesium alloy melt obtained in step 2 into a preheated mold to form a magnesium alloy ingot after cooling; Step 4: heating and homogenizing the magnesium alloy ingot obtained in step 3; Step 5: the magnesium alloy treated in step 4 is extruded at 350° C. to 450° C., with an extrusion rate of 1 to 10 mm / s and an extrusion ratio of 10 to 50; Step 6: The magnesium alloy treated in step 5 is subjected to a heat treatment at 300°C-450°C for 1-12 hours, and subjected to a pre-compression deformation treatment; wherein, the pre-compression deformation is 1%-15% calculated according to the percentage of length change, and the strain rate is 10 -2 ~10 -4 / s; Step 7: heat-treating the magnesium alloy obtained in step 6 to obtain the magnesium alloy material.

2. The method according to claim 1, characterized in that: In step 1, pure Mg is melted at 700°C to 720°C; the inert gas is a mixed gas of CO2 and SF6; after the inert protective gas is introduced, the temperature is kept at 650°C to 700°C for 20 to 40 minutes.

3. The method according to claim 2, characterized in that: In the mixed gas, the volume ratio of CO2 and SF6 is (200~400):

1.

4. The method according to claim 1, characterized in that: In step 2, the melt is heated to 720° C. to 750° C. and then kept warm.

5. The method according to claim 1, characterized in that: In step 3, the mold is preheated to 200°C to 350°C.

6. The method according to claim 1, characterized in that: In step 4, the conditions for the heating homogenization treatment are: homogenization treatment at 400° C. to 480° C. for 8 h to 24 h.

7. The method according to claim 1, characterized in that: In step 7, the heat treatment is: keeping warm at 100° C. to 260° C. for 2 h to 24 h.

8. The method according to claim 1, characterized in that: Calculated by mass percentage, in the magnesium alloy material, the Zn content is 0.5% to 1%, the Ca content is 0.1% to 0.3%, the Nd content is 0.3% to 0.6%, and the remainder is magnesium and unavoidable impurity elements.

9. The method according to claim 1, characterized in that: The ultimate compression rate of the magnesium alloy material at room temperature is at least 30%.